Perception of mental health in Pakistani nomads: An interpretative phenomenological analyses - Choudhry, Riaz Fahad; Bokharey, Iram Zehra (Taylor & Francis, 2013)
The study was conducted to explore the mental health issues of Pakistani nomads and to uncover their concept, ideation,and perception about mental health and illnesses. It was an exploratory study situated in the qualitative paradigm. The research strategy used was Interpretative Phenomenological Analysis (IPA), as the study was planned to explore the lived experiences of nomads regarding mental health and coping strategies and how they interpret those experiences. For data collection, focus group discussions (FGDs) were conducted. Seven participants were included in the FGDs, and two FGDs were conducted composed of both genders. The responses were recorded, and data were transcribed and analysed using IPA. Data verification procedures of peer review, which help to clarify researcher bias and rich thick description, were used. The major themes were lack of resources and myriad unfulfilled needs, specifically the basic needs (food, shelter, and drinking and bathing water). Moreover, a strong desire to fulfil the secondary needs of enjoyment and having luxuries was also reflected. A list of recommendations was forwarded for policy making of this marginalized community and to create awareness regarding mental health.